Diversity and Distribution Patterns of Dragonflies in The Region Bagek Kembar Ecotourism, Sekotong - Pebrianti, Hasita; Ilhamdi, Mohammad Liwa; Yamin, M. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Dragonflies have an important role as environmental bioindicators, especially as indicators of the success of mangrove ecosystem restoration projects and their distinctive color has becomes an ecotourism attraction, so this research is important to do. This research aims to determine the diversity and distribution patterns of dragonflies in the Bagek Kembar Sekotong Mangrove Ecotourism area. This is an explorative descriptive study and was carried out between December 2023-January 2024. The research method used was catching dragonflies with insect nets following three transect paths along the river flow in the Bagek Kembar Sekotong Mangrove Ecotourism area. Analysis of species diversity data using the Shannon Wiener diversity index and calculation of the dragonfly distribution pattern index using the variance test. Based on the research results, 9 species of dragonflies were obtained, including 8 species of dragonflies (Anisoptera) and 1 species of dragonflies (Zygoptera). The diversity index (H') of dragonflies at the observation location is 1,866. The conclusion is that diversity of dragonflies at the research location is in the medium category. The distribution pattern of dragonflies at the research location shows that one Potamarcha congener species has a regular distribution pattern and the other 8 species that had groups distribution pattern.